2011
DOI: 10.17763/haer.81.2.t022245n7x4752v2
|View full text |Cite
|
Sign up to set email alerts
|

Inside the Double Bind: A Synthesis of Empirical Research on Undergraduate and Graduate Women of Color in Science, Technology, Engineering, and Mathematics

Abstract: review nearly forty years of scholarship on the postsecondary educational experiences of women of color in science, technology, engineering, and mathematics (STEM). Their synthesis of 116 works of scholarship provides insight into the factors that influence the retention, persistence, and achievement of women of color in STEM fields. They argue that the current underrepresentation of women of color in STEM fields represents an unconscionable underutilization of our nation's human capital and raises concerns of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
712
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 769 publications
(742 citation statements)
references
References 41 publications
(75 reference statements)
29
712
0
1
Order By: Relevance
“…These environments for women are likely to be different and constitute an area for future study. Our numbers did not allow us to consider the unique experiences of racial and ethnic minority women in STEM graduate programs, an area critically important to explore for deeper understanding of how multiple marginalities affect experience and science career intentions (McGee et al 2016;Ong et al 2011). Additionally, our sample and promise of confidentiality prevented us from examining the experiences of international students or exploring disciplinary factors.…”
Section: Limitationsmentioning
confidence: 98%
See 2 more Smart Citations
“…These environments for women are likely to be different and constitute an area for future study. Our numbers did not allow us to consider the unique experiences of racial and ethnic minority women in STEM graduate programs, an area critically important to explore for deeper understanding of how multiple marginalities affect experience and science career intentions (McGee et al 2016;Ong et al 2011). Additionally, our sample and promise of confidentiality prevented us from examining the experiences of international students or exploring disciplinary factors.…”
Section: Limitationsmentioning
confidence: 98%
“…Identifying as a female and a member of a traditionally male-dominated field deviates from or is incompatible with the norms for both (Cadsby et al 2013;Danielsson and Linder 2009;Gonsalves 2014). Women of color in STEM graduate studies face additional stereotypes that run counter to the prototypical white male in science, what scholars have referred to as the "double-bind", further oppressing their identity as a member of science culture (Malcom et al 1976;Ong et al 2011). In a study of diary entries and attitudinal measures of entering female undergraduates, when STEM was viewed as incompatible with feminine identity, motivation to continue in science careers decreased (London et al 2011).…”
Section: The Gendered Culture Of Stem Graduate Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, numerous projects were set [6,9,12,13,18,25,26] An in-depth and longitudinal study conducted at an NSF funded Engineering Research Center showed that university faculty are persistent to change their teaching approaches no matter they had attended numerous professional development activities over couple years [11]. Faculty who reported dramatic changes in their teaching approaches were the ones who worked in collaboration with the learning scientists and systematically designed their own evidence based instruction in their own classrooms; collected data from their students with the help of the learning scientists, and published their educational design study results in journals or presented at educational conferences.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, in a review of research on minority retention, Ong, Wright, Espinosa, and Orfield (pp. 188-189) noted "agency and personal drive" as a major resource for women of color in STEM undergraduate programs 4 . This personal quality was conceptualized not as purely individualistic but as tapping into identity in a marginalized community for empowerment.…”
Section: Introductionmentioning
confidence: 99%